Effects of annealing temperature and time on the P-Type silicon wafer with Boron & Phosphorus dopants / Nurul Nadia Che Manaf - Che Manaf, Nurul Nadia (2010)
This project is study on annealing of temperature and time variation on P type silicon wafer by using dopants of Phosphorus and Boron. The properties that being analyses are sheet resistivity and conductivity of sample after diffusion process. Conductivity is a property which describes the ability of a material to conduct current while sheet resistivity is a measure of resistance of thin film that has a uniform thickness. It is commonly used to characterize materials made by semiconductor doping, and is one of the most important properties to determine the conductivity. This project study is about the effect of sample after added dopant onto the P type wafer. Dopants type that used in this project is dopant of P type and N type which are Phosphorus and Boron. The dopant being added onto desired wafer surface by using spin on dopant. After completing the spin on dopant process, the testing samples undergo diffusion process which is to introduce the dopant into silicon surface by using high temperature. Then, dopants can diffuse into the silicon substrate, which changes the conductivity of semiconductor. After diffusion process was completed, the testing samples undergo four point probes testing to determine the sheet resistivity of the sample.